Porównywanie wariantów podziału głosów w grach głosowania z przedstawicielstwem - Korzeniowski, Arkadiusz (Comparing Voice Distribution among Council in Two-Tier Composite SVG, 2006)
First we present Felsenthal and Machover's model of a two-tier composite SVG and a theorem of optimal (reflecting the ..direct democracy" within all constituencies) voice distribution in the council of representatives. Further, from the definition of the mean majority deficit Δ[W] of Felsenthal-Machover, the author proposes a method to compare decision rules V in a W = [W1,...,Wm]. Additionally the author introduces index of disharmony s [W] to measure the probability that in a division of the council a bill will pass/fail against the majority. With the help of s[V] he confronts different two-tier composite SVG W=V[W1,...,Wm] and the distribution V of voices in given W=V[W1,...,Wm].
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 166-175